2022
DOI: 10.1093/aob/mcac100
|View full text |Cite
|
Sign up to set email alerts
|

Cost–benefit analysis of mesophyll conductance: diversities of anatomical, biochemical and environmental determinants

Abstract: Background Plants invest photosynthates in construction and maintenance of their structures and functions. Such investments are considered costs. These costs are recovered by CO2 assimilation rate (A) in the leaves and thus A is regarded as the immediate, short-term benefit. In photosynthesising leaves, CO2 diffusion from the air to the carboxylation site is hindered by several structural and biochemical barriers. CO2 diffusion from the intercellular air space to the chloroplast stroma is obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 166 publications
1
14
0
Order By: Relevance
“…Further bicorrelation analysis between g m_ fluo and leaf anatomical traits showed that no leaf anatomical traits were correlated with g m across species except chloroplast thickness (Figure 4). Although several studies claimed that CO 2 diffusion resistance in stroma could be low because its high pH and Rubisco concentrations could facilitate CO 2 diffusion (Mizokami et al, 2022;Terashima et al, 2011), here I observed that g m was negatively correlated with stroma thickness, similar to other studies (Liu et al, 2021;Tosens, Niinemets, Vislap, et al, 2012;Veromann-J ürgenson et al, 2020).…”
Section: Leaf Anatomical Traits Cannot Fully Explain Mesophyll Conduc...supporting
confidence: 90%
See 1 more Smart Citation
“…Further bicorrelation analysis between g m_ fluo and leaf anatomical traits showed that no leaf anatomical traits were correlated with g m across species except chloroplast thickness (Figure 4). Although several studies claimed that CO 2 diffusion resistance in stroma could be low because its high pH and Rubisco concentrations could facilitate CO 2 diffusion (Mizokami et al, 2022;Terashima et al, 2011), here I observed that g m was negatively correlated with stroma thickness, similar to other studies (Liu et al, 2021;Tosens, Niinemets, Vislap, et al, 2012;Veromann-J ürgenson et al, 2020).…”
Section: Leaf Anatomical Traits Cannot Fully Explain Mesophyll Conduc...supporting
confidence: 90%
“…As discussed in many recent studies (Evans, 2021; Evans et al., 2009; Mizokami et al., 2022), the CO 2 diffusion conductance can be potentially enhanced by many other factors, such as specific protein channels in membranes, fast conversion of CO 2 to bicarbonate catalyzed by CAs in the cytosol and stroma, and concentrated Rubisco in the stroma. Therefore, the term that accounts for the effect of facilitation of CO 2 transport in each component can be expressed as follows:gnormali=normalρnormaliDnormalγnormalinormalτnormaliΔLnormali1+normalϵi,where ε i is defined as the enhancement due to facilitation processes in that component (Evans et al., 2009); ε was rarely considered in previous studies because of difficulties in the estimation of those values.…”
Section: Methodsmentioning
confidence: 99%
“…Although it is difficult to directly measure CO 2 concentrations at the cellular level, microscopic measurements of chlorophyll fluorescence can inform us on the extent of CO 2 heterogeneity in plant cells. An evaluation of the costs and benefits of CO 2 ‐relocation will require analyses of factors such as cytoskeletal energetics (Hill & Kirschner, 1982; Leighton & Sivak, 2022; Okamoto & Lightfoot, 1992) and the cellular CO 2 conductance (Mizokami et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…This situation would result in the conditional CO 2 heterogeneity, and chloroplasts would show the CO 2 -tactic movements towards the water-free surfaces, which would be effective not only in increasing the CO 2 supply to the chloroplasts but also in avoiding photoinhibition of the chloroplasts. The cost-benefit analysis of CO 2 -relocation will require the discussion in context of the cytoskeletal energetics (Hill & Kirschner, 1982;Okamoto & Lightfoot, 1992;Leighton & Sivak, 2022) and evaluation of the cellular CO 2 conductance (Mizokami, et al, 2022).…”
Section: Ecological Aspect Of Co 2 Relocationmentioning
confidence: 99%